To end a presidency the power of impeachment - Tribe, Laurence H.; Matz, Joshua (Basic Books, 2018)
"The history and future of our democracy's ultimate sanction, presidential impeachment, and a guide to how it should be used now. To End a Presidency addresses one of today's most urgent questions: when and whether to impeach a president. Laurence Tribe and Joshua Matz provide an authoritative guide to impeachment's past and a bold argument about its proper role today. In an era of expansive presidential power and intense partisanship, we must rethink impeachment for the twenty-first century. Of impeachments, one Constitutional Convention delegate declared, "A good magistrate will not fear them. A bad one will be kept in fear of them." To End a Presidency is an essential book for all Americans seeking to understand how this crucial but fearsome power should be exercised"-- Provided by publisher.